Alcohol withdrawal detox with focus on drugs used for its management - MANJU ASWATH; RADHIKA MADHUSOODAN (International Journal of Pharma and Bio Sciences, 2018)
Alcohol withdrawal is commonly encountered in general hospital settings. It forms a major part of referrals received by a consultation-liaison psychiatrist. This article aims to review the evidence base for appropriate clinical management of the alcohol withdrawal syndrome. Alcohol withdrawal syndrome is a clinical diagnosis. It may vary in severity. Complicated alcohol withdrawal presents with hallucinations, seizures or delirium tremens. Benzodiazepines have the best evidence base in the treatment of alcohol withdrawal, followed by anticonvulsants. Alcohol withdrawal syndrome (AWS) is a distressing condition, generally controlled by benzodiazepines (BZD’s). Baclofen, a gamma-aminobutyric acid-B (GABAB) agonist, has also shown promising results in controlling AWS. Clinical institutes withdrawal assessment-alcohol revised score (CIWA-Ar score) is useful in assessing pitfalls in patients with medical comorbidities along with alcohol withdrawal symptoms. Evidence favors an approach of symptom-monitored loading for severe withdrawals where an initial dose is guided by risk factors for complicated withdrawals and further dosing may be guided by withdrawal severity. Supportive care and use of vitamins is also found of little benefit.